Comparison of transcriptome profiles of radiotherapy beams on MCF-7 breast cancer xenografts - Koprulu, Tugba Kul; Aras, Serhat; Cam, Burcin Erkal; Kara, Altan (SPRINGER JAPAN KK, 2025)
The objective of this study was to investigate the acute radiobiological mechanisms underlying Flattening Filter (FF) and Flattening Filter Free (FFF) radiotherapy-induced inhibition of breast cancer (BCa) by detecting changes in gene expression levels. The study involved thirty-six adult nude mice models that were randomly divided into five groups: control (G1), breast cancer (BCa) (G2), FF-400 (G3), FFF-1120 (G4), and FFF-1820 (G5). The control group had no radiation or treatment, while the BCa group had a cancer model but no radiation. The BCa models were subjected to a single dose of 20 Gy of radiotherapy at varying dose rates: 400, 1120, and 1820 MU/min (G3, G4, and G5, respectively). Twenty days after implantation of the MCF-7 cancer cell line, nude mice were irradiated and sacrificed 48 h later for genetic analysis. A transcriptome library was created by extracting RNA from tissue samples. In the differentially expressed genes (DEG) analysis, a total of 1565 genes were found to be significantly altered in the G2 vs. G1 groups. When radiotherapy groups (G3, G4, and G5) were analyzed, 334 DEGs (231 down, 103 up) were identified in G3 vs G2 data, 167 DEGs (103 down, 64 up) in G4 vs G2 data, and 187 DEGs (116 down, 71 up) in G5 vs G2 data. Gene Ontology molecular function analysis revealed significant differences between groups G3 and G2, with an emphasis on protein binding, glutamate receptor activity, and interleukin-8 receptor activation. Similar features were observed when comparing groups G5 and G2. The analysis showed significant differences in the expression of the key ERAD pathway genes Ufd1 and Cav1 between the BCa and radiotherapy groups. It was concluded that the FFF beam significantly alters the processes underlying the ERAD pathway and glutamate receptor activation compared to the FF beam.
Keywords: Radiotherapy; Breast cancer; Xenografts; Transcriptome; Next Generation Sequencing; DOSE-RATE; FLATTENING-FILTER; IN-VITRO; IRRADIATION; PULSE; Oncology; Obstetrics & Gynecology